SUPPLY CHAIN RISK ANALYSIS IN INTERIOR DESIGN SME IN INDONESIA - Sanny, Lim; Prajna, Anderson; Gunawan, Daniel; Prayoga, Malvin (International Journal of Supply Chain Management, 2020)
At present, interior design SME in Indonesia is one of the most rapidly developing SMEs in Indonesia, but this great potential is also accompanied by a high risk, especially in supply chain. The purpose of this study is to analyze risks, find out the causes of the risk, and recommend the best mitigation strategies that can be done in the supply chain of SME interior design. The method used for this research is mixed research method and the type of research used is descriptive research. Data analysis was carried out using SCOR level 1 method with HOR approach. Level 1 SCOR is used for activity mapping. The House of Risk (HOR) approach is divided into 2 stages, in which phase 1 begins with identifying the risks of the problems that have been experienced by interior design SMEs in Indonesia. After obtaining the ten cause of risks that exist, measures of severity and correlation will be carried out. Finally, Aggregate Risk Potential (ARP) is calculated to find out the most dangerous cause of risk, which is distance traveled. HOR stage 2 begins with the evaluation of the most dangerous cause of risks from the results of ARP calculations. This stage focuses on choosing the most effective handling strategy, which is to encourage the efficiency of shipping by only making one delivery of goods.